How to make a mountain : in just 9 simple steps and only 100 million years! - Huntington, Amy (Chronicle Kids, 2022)
"Geology and earth science made easy (to learn) and super-quick (to read about). You, too, can make a mountain--start today! (Some restrictions apply.)"--